Coffee intake may promote sudomotor function activation via the contribution of caffeine - Kwon, Ryeo-Won; Park, Jin-Sun; Lee, Ha-Gyoung; Park, Jong-In; Choo, Eon-Ah; Lee, Seung-Jea; Lee, Jeong-Beom (Frontiers in Nutrition, 2022)
Objectives To determine whether drinking coffee with caffeine accelerates the sympathetic response to acetylcholine (ACh). Methods Tests were performed twice at 1-week intervals following the intake of coffee. Subjects were randomly divided into two groups: Group A was administered 16 fluid oz of water (CON), while Group B was given 16 fluid oz of coffee (Coffee). After 1 week, Group A was administered 16 fluid oz of coffee (Coffee), while Group B was given 16 fluid oz of water (CON). The quantitative sudomotor axon reflex test (QSART) was performed after intake of coffee and water and a 40 min break. QSART with iontophoresis and 10% ACh was performed to determine axon reflex (AXR) mediated with and without iontophoresis [AXR (1) and AXR (2), respectively], and directly activated sweating (DIR). Results The sweat onset time of the AXR was shorter in the Coffee compared with the CON (p < 0.05). The sweat rates in AXR (1) AXR (2) and DIR were significantly higher in the Coffee than in the CON (p < 0.05, p < 0.05, p < 0.01, respectively). In addition, the Coffee showed significantly higher density of activated sweat glands and activated sweat gland output than the CON (p < 0.05, p < 0.01, respectively). The overall results of this study showed that coffee intake could stimulate higher activation in both AXR and DIR sweat responses. Conclusion Coffee intake can improve sweating sensitivity in both the AXR and DIR by the contribution of caffeine contained in coffee. This suggests that other compounds in coffee may not inhibit the sympathetic response to ACh. Therefore, coffee may be clinically worth considering as a supplement for the activation of the cholinergic and sudomotor function.